The Maize DWARF1 Encodes a Gibberellin 3-Oxidase and Is Dual Localized to the Nucleus and Cytosol . Issue 4 (23rd October 2014) - Chen, Yi; Hou, Mingming; Liu, Lijuan; Wu, Shan; Shen, Yun; Ishiyama, Kanako; Kobayashi, Masatomo; McCarty, Donald R.; Tan, Bao-Cai
Abstract : Bioactive GAs can be synthesized in the cytosol and the nucleus . Abstract: The maize ( Zea mays ) gibberellin (GA)-deficient mutant dwarf1 ( d1 ) displays dwarfism and andromonoecy (i.e. forming anthers in the female flower). Previous characterization indicated that the d1 mutation blocked three steps in GA biosynthesis; however, the locus has not been isolated and characterized. Here, we report that D1 encodes a GA 3-oxidase catalyzing the final step of bioactive GA synthesis. Recombinant D1 is capable of converting GA20 to GA1, GA20 to GA3, GA5 to GA3, and GA9 to GA4 in vitro. These reactions are widely believed to take place in the cytosol. However, both in vivo GFP fusion analysis and western-blot analysis of organelle fractions using a D1-specific antibody revealed that the D1 protein is dual localized in the nucleus and cytosol. Furthermore, the upstream gibberellin 20-oxidase1 (ZmGA20ox1) protein was found dual localized in the nucleus and cytosol as well. These results indicate that bioactive GA can be synthesized in the cytosol and the nucleus, two compartments where GA receptor Gibberellin-insensitive dwarf protein1 exists. Furthermore, the D1 protein was found to be specifically expressed in the stamen primordia in the female floret, suggesting that the suppression of stamen development is mediated by locally synthesized GAs.